Failure of Fenbedazole and Ivermectin to Control Gastrointestinal Nematodes in Goats in Rewa, Madhya Pradesh - Chaurasiya, Rupesh; Dixit, Pooja; Dixit, Alok K (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Anthelmintic resistance has been reported in most goat-raising areas in India, yet little is known about the anthelmintic resistance status  in gastrointestinal nematodes in goats in Rewa, Madhya Pradesh. The aim of this study was to determine the occurrence of anthelmintic  resistance in goats in field conditions using Faecal Egg Count Reduction test (FECRT). 40 goats having egg per gram above 600 were  divided into a control (G1) and three treatment groups (G2, G3 and G4) consisting of 10 goats in each group. Goats which were not  given any treatment were kept as control group. Group G2, G3 and G4 goats were treated with fenbendazole @ 7.5 mg/kg BW orally,  closantel @ 10 mg/kg BW orally and ivermectin @ 0.2 mg/kg BW subcutaneously, respectively. Percent reduction in faecal egg counts  were monitored 14 days after treatment. The FECRT indicated percent reductions of 83, 94 and 94 for G2, G3 and G4, respectively. When  analysed statistically using standard WAAVP protocol, anthelmintic resistance against fenbendazole and ivermectin was detected.  These findings strongly suggest that anthelmintic resistance is a serious problem in strongyles in goats in Rewa and marked changes  in gastrointestinal nematode management need to be instituted immediately to mitigate a worsening situation.
Keywords: Anthelmintic resistance; Fenbendazole,; Gastrointestinal nematodes; Goats,; Ivermectin